2020
DOI: 10.1039/c9ta10779g
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of co-sensitizers in a copper bipyridyl redox system for efficient and cost-effective dye-sensitized solar cells in solar and ambient light

Abstract: Co-sensitization can reduce the cost of a dye-sensitized solar cell, while maintaining high efficiency: up to 29% in ambient light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 55 publications
0
57
0
Order By: Relevance
“…In recent years, DSCs have been established as a highly promising alternative for diffuse and low light conditions. [ 2–4 ] DSCs are currently the most efficient solar cell technology in low light conditions, which makes them excellent candidates for building and automobile integrated photovoltaics and to power sensors, appliances for the Internet of Things (IoT), and portable devices. [ 5–10 ] Recent developments of new photoanodes, counter electrodes, dyes, and co‐adsorption strategies have further improved device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, DSCs have been established as a highly promising alternative for diffuse and low light conditions. [ 2–4 ] DSCs are currently the most efficient solar cell technology in low light conditions, which makes them excellent candidates for building and automobile integrated photovoltaics and to power sensors, appliances for the Internet of Things (IoT), and portable devices. [ 5–10 ] Recent developments of new photoanodes, counter electrodes, dyes, and co‐adsorption strategies have further improved device efficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…1) 27 was selected as the sensitizer for the following reasons: (1) the optimal lm thickness (8 mm) is smaller than for other dyes such as N719 (20 mm), 28 greatly reducing the materials cost and cell fabrication time; (2) it revealed superior performance to other dyes tested in the solid-state DSSC structure adopted in this study; (3) its performancecost ratio has been reported to be high. 29 The unsealed DSSCs reached a maximum peak PCE of 5.2% (average 4.9%) and stabilized (stb.) PCE of 5.0% (average 3.6%).…”
Section: Introductionmentioning
confidence: 93%
“…When used together with a Cu(tmby) 2 electrolyte, a 3.2 cm 2 DSC with this dye combination achieved a PCE of 29% at 1000 lx. 52 As stated at the beginning of this section, requirements for indoor dyes are different than those for outdoor ones. Looking at future dye design, from a purely light absorption point of view, and looking at the lamp emission in Fig.…”
Section: Sensitizersmentioning
confidence: 99%